The Relationship Between Social Anxiety and Phubbing Behavior Among Public Senior High School Students in Sleman Regency - Shinta Dwi Sarlini; Sigit Sanyata (Journal of Educational Sciences, 2026)
This study aims to determine the relationship between social anxiety and phubbing behavior among public high school students in Sleman Regency. This study is a correlation study. The study population consists of public high school students in Sleman Regency from 8 schools with a total of 4,492 students. A sample of 354 students was selected using proportional random sampling. Data collection methods used the SAS-A (Social Anxiety Scale for Adolescents) and the Phubbing Scale. Validity testing was conducted using Expert Judgment. The reliability test used the Cronbach's alpha technique, obtaining p=0.924 for the social anxiety variable and p=0.924 for the phubbing behavior variable. The data were analyzed using descriptive statistics and simple regression with the SPSS 22 For Windows program. The results showed a positive and significant relationship between social anxiety and phubbing behavior, with a correlation coefficient of 0.292 and a p-value <0.05, meaning that higher social anxiety was associated with higher phubbing behavior. Additionally, the coefficient of determination was 0.085, indicating that social anxiety contributed 8.5% to phubbing behavior. These findings indicate that social anxiety plays an important role in shaping students’ phubbing behavior and highlight the importance of preventive intervention programs in educational settings.